Management of raised blood pressure in New Zealand: a discussion document. Issue 6896 (10th July 1993) - Jackson, R; Barham, P; Bills, J; Birch, T; McLennan, L; MacMahon, S; Maling, T
Abstract : A report to the National Advisory Committee on Core Health and Disability Support Services, New Zealand, on the management of raised blood pressure recommends that decisions to treat raised blood pressure should be based primarily on the estimated absolute risk of cardiovascular disease rather than on blood pressure alone. In general, patients with a blood pressure of 150-170 mm Hg systolic or 90-100 mm Hg diastolic, or both, should be given treatment to lower blood pressure if the risk of a major cardiovascular disease event in 10 years is more than about 20%. The results of clinical trials indicate that, at this level of absolute risk, 150 people would require treatment to reduce the annual number of cardiovascular events by about one. Implementation of these recommendations may result in a smaller proportion of people aged under 60, particularly women, receiving treatment but an increased proportion of older people treated. In the absence of specific contraindications, low dose diuretics and low dose beta blockers should be considered for first line treatment, since for only these drug groups is there direct evidence of reduced risk of stroke and coronary disease in people with raised blood pressure.